Spatial–Temporal Impacts of Urban Sprawl on Ecosystem Services: Implications for Urban Planning in the Process of Rapid Urbanization - Xiaoyan Li (MDPI AG, 2021)
Rapid urbanization drives land cover change, affecting urban ecosystems and inducing serious environmental issues. The study region of Changchun, China was divided into three urbanization categories according to different urbanization levels and the characteristics of urban sprawl and changes and relationships between typical ecosystem services (ESs) under rapid urbanization were analysed. The results showed that Changchun has undergone considerable urban expansion since 2000, which has significantly impacted all ESs in terms of spatial and temporal heterogeneity. Habitat suitability and crop yield have relatively stronger service capacity in the study area. Since the expansion of large-scale infrastructures, the mean ES values of developed urban areas are the lowest among the three zones, except for water retention and sandstorm prevention in 2015, when the balance between all services decreased. Over the past 16 years, habitat suitability in developing urban areas has decreased to a large extent due to urban sprawl. Because of the improvement in agricultural science and technology, crop yield in three regions increased, while the area of cropland reduced from 1720 km2 to 1560 km2 (9.3%). Synergies between habitat suitability and carbon storage and habitat suitability and soil retention were detected in three areas. A trade-off between habitat suitability and water retention was detected in three areas. The interactions between crop yield and carbon storage, habitat suitability, and soil retention were more complex in this study region. In addition to water retention, urbanization index has a negative correlation with ESs. According to the results, some suggestions to alleviate ES loss during the process of rapid urbanization were proposed, which may guide scientific urban planning for sustainable urban development.